The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12904-020-00643-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors underlying surrogate medical decision-making in middle eastern and east Asian women: a Q-methodology study

Abstract: Background: It is not clear how lay people prioritize the various, sometimes conflicting, interests when they make surrogate medical decisions, especially in non-Western cultures. The extent such decisions are perspective-related is also not well documented. Methods: We explored the relative importance of 28 surrogate decision-making factors to 120 Middle-Eastern (ME) and 120 East-Asian (EA) women from three perspectives, norm-perception (N), preference as patient (P), and preference as surrogate decision-make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“… 6 , 51 Families are often the main carers for patients diagnosed with cancer in the Middle East and also take responsibility for treatment, 6 compared with Western countries, where care and treatment choices are more strongly dependent on patient preferences and where hospices or nursing homes are more acceptable and available. 52 One study in Taiwan showed that older Taiwanese residents at long-term care institutions believe firmly that they must contact their families before making any decisions connected to end-of-life care, in contrast to older Europeans and Americans, 53 , 54 while another study showed that family members participated in decision making in <50% of all non-Hispanic White patients with cancer, with percentages being higher for Asian Americans and Spanish-speaking Latinos. 55 Therefore, while raising awareness of different cancers, there should be more consideration of the impact that family members and friends have on lifestyle choices and behaviors.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 51 Families are often the main carers for patients diagnosed with cancer in the Middle East and also take responsibility for treatment, 6 compared with Western countries, where care and treatment choices are more strongly dependent on patient preferences and where hospices or nursing homes are more acceptable and available. 52 One study in Taiwan showed that older Taiwanese residents at long-term care institutions believe firmly that they must contact their families before making any decisions connected to end-of-life care, in contrast to older Europeans and Americans, 53 , 54 while another study showed that family members participated in decision making in <50% of all non-Hispanic White patients with cancer, with percentages being higher for Asian Americans and Spanish-speaking Latinos. 55 Therefore, while raising awareness of different cancers, there should be more consideration of the impact that family members and friends have on lifestyle choices and behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…But the patients still preferred the shared family decision making model. (AlHaqwi et al, 2015;Hammami et al, 2020) Family caregivers' behaviours during D.M process may be seen as a continuum from a passive to an active attitude. Most of the patients, FCs and physicians prefer the FCs to be involved in treatment decision-making (Dionne-Odom et al, 2019;Lamore et al, 2017).…”
Section: Introductionmentioning
confidence: 99%